Growth Dependent Changes in Pressure Sensing Walkway Data for Turkeys - Kremer, Jody A.; Robison, Cara I.; Karcher, Darrin M. (Frontiers in Veterinary Science, 2018)
Genetic selection for rapidly growing turkeys has created an unintentional consequence impacting the skeletal system resulting in long bone distortions. These distortions have resulted in locomotor problems, gait abnormalities, leg weakness or lameness issues. These effects raise welfare issues along with animal agriculture inefficiency in the form of lost product. The purpose was to determine baseline gait and force distribution in visibly unimpaired growing turkey hens. Hendrix commercial turkey hen poults (n=100) were placed on pine wood shavings providing 0.78m2 per bird with ad libitum access to feed and water at the MSU Poultry Farm. Fifty hens were randomly selected at 5 wk and identified with a leg band to ensure longitudinal data collection. The turkeys were walked across a pressure-sensing walkway (PSW, Tekscan, Boston, MA), one to three times and weighed at 5, 6, 8, and 10 wk of age. PSW collected data on gait length, gait time, step force and step length and the statistics were analyzed with SAS. Both temporospatial data, including step time and step length, and kinetic data, including peak downward force and vertical impulse, were recorded. Body weight increased linearly with age (P<0.001), demonstrating a typical growth pattern. Gait cycle time and peak vertical force all displayed no difference between right and left sides, indicating that the hens had no detectable gait abnormalities. Gait velocity increased with age (P=0.02) suggesting hens’ growth impacted their gait velocity. The gait cycle time (P<0.01) did not correspond with age. Peak vertical force (PVF) increased linearly with age (P<0.01) from 6 wks (2.23 kg) to 10 wks of age (5.91 kg). PVF/kg body weight (P<0.01) increased from 6 wks of age (96.9 % BW) to 8 wks of age (106 %BW). Overall, the birds were not lame and some data was influenced by the hen’s adjustment to the materials or stage of growth; in contrast, some temporospatial data did not coincide with age. The PSW could be used to detect locomotor issues in commercially produced turkey hens providing another tool for assessing well-being.